Study on evaluation of current status and awareness of farmers at lobster cage culture areas in Xuan Dai bay, Phu Yen province - Hoang , Thi My Huong; Nguyen, Phu Hoa (Journal of Technical Education Science, 2019)
The current status and awareness of farmers about lobster cage culture in Xuan Dai Bay, Phu Yen Province was conducted based on a Participatory Rural Appraisal questionnaire (PRA).The survey results show that lobster cages culture in the research areas took place in a long time, from 10 to more than 20 years and increasing in number and size. However, the awareness of farmers about aquaculture activities and water environment protection is still low. The culture level of the farmers is rather low, the concentration in the secondary level accounts for 61.8%. The 100% experience of lobster cage culture of the farmers are quite studied by themselves from reality and from others without the adoption from any training programs. 99% of the farmers have lobster farming, followed by 100% of households. Cultivation density/cages and the number of spontaneous cages not included in the planning area are also increasing rapidly. Although, 100% of farmers think that the main cause of disease in lobster is due to the quality of water and 70.6% of households think that the food is left over. However, 72% of farmers did not care about water quality and 81.7% did not handle leftover food. 100% of lobster farmers do not use any chemicals to improve the water and 100% of farmers do not equip water treatment equipment. In addition, 30% of farmers do not respond to the planning of farming areas.